2009
DOI: 10.1111/j.1472-8206.2009.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory and anti‐peroxidative roles of diacerein are possibly mediated through an alteration in thyroid functions in animal model of inflammation

Abstract: This study was designed to reveal the possible involvement of thyroid hormones, if any, in diacerein induced alterations in glucose metabolism and tissue lipid peroxidation (LPO) in the animal model of carrageenan-induced inflammation. We studied the influence of diacerein administration on the changes in carrageenan-induced thyroid dysfunction; hepatic, renal and cardiac LPO as well as serum glucose, thyroid hormones and insulin concentrations in Wistar rats. Alterations in paw volume, serum levels of total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
3
7
1
3
Order By: Relevance
“…In this study, T4 was decreased significantly due to oral intake of carrageenan and that results are in accordance with Jatwa & Kar, (2009), who observed significant decrease in the serum concentrations of T4 following carrageenan administration. Carrageenan is known to induce inflammation, which resulted in depressed activity of thyroid gland (Borthakur et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, T4 was decreased significantly due to oral intake of carrageenan and that results are in accordance with Jatwa & Kar, (2009), who observed significant decrease in the serum concentrations of T4 following carrageenan administration. Carrageenan is known to induce inflammation, which resulted in depressed activity of thyroid gland (Borthakur et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Carrageenan-induced hypothyroidism appears to be an outcome of increased IL-1 level, which in turn decreases serum concentration of T4 and T3 (Singh et al, 2014). The level of serum T4 level was significantly increased by administration of diacerein in group V. Jatwa & Kar, (2009) found that the levels of both thyroid hormones were regulated after diacerein administration. Their study concluded that administration of diacerein with Carageenan regulates thyroid functions both at the glandular level (the only source of T4 generation) and at the level of peripheral conversion of T4 to T3 (the major process of T3 formation).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…На фоне терапии диацереи-ном достоверно улучшились показатели липидограммы -снизились уровни ЛПНП (р < 0,001) и ТГ (р < 0,01). Полученные данные не противоречат литературным и связаны с плейотропными эффектами препарата [29,41]. А.В.…”
Section: Discussionunclassified
“…Наши результаты соответствуют данным, полученным другими исследователями, которые считают, что диаце-реин может участвовать в регуляции деятельности щито-видной железы [41]. В ряде работ, в т. ч. эксперименталь-ных, было подтверждено [29,41], что при приеме препа-рата наблюдается положительная динамика, связанная с нормализацией концентраций гормонов щитовидной железы. Однако механизмы развития данного эффекта точно не установлены, что требует дальнейшего изучения данного вопроса.…”
Section: Discussionunclassified